Initiatives to Establish a Zero-Tolerance Sexual Violence Policy at State Islamic University - Rochimah; Mahzumi, Fikri; Naf’an, Abdul Wahab (LETIGES, 2026)
This study seeks to establish a zero-tolerance environment for sexual violence at UIN Sunan Ampel Surabaya by enhancing internal processes based on Islamic campus principles. It addresses ongoing concerns of sexual violence and the lack of effective preventive and response procedures, highlighting the significance of gender awareness and justice for victims. This study employed a Participatory Action Research (PAR) approach, grounded in the social-ecological model, comprising four stages: planning, action, observation, and evaluation. Stakeholders across the institution contributed to policy development, education, awareness campaigns, and the formation of a Sexual Violence Prevention and Handling Task Force (Satuan Tugas Pencegahan dan Penanganan Kekerasan Seksual/Satgas PPKS). Continuous evaluation enabled improvements at each phase. The findings show that campus members' awareness of sexual violence remains low, with misunderstandings regarding its forms and consequences. The study yielded significant results through participatory action, including the formation of a gender-responsive task force, policy proposals, gender education initiatives, and a